Design, synthesis, and biologic evaluation of novel galloyl derivatives as HIV‐1 RNase H inhibitors. (24th January 2019) - Gao, Ping; Wang, Xueshun; Sun, Lin; Cheng, Xiqiang; Poongavanam, Vasanthanathan; Kongsted, Jacob; Álvarez, Mar; Luczkowiak, Joanna; Pannecouque, Christophe; De Clercq, Erik; Lee, Kuo‐Hsiung; Chen, Chin‐Ho; et al.
Abstract: Human immunodeficiency virus (HIV) reverse transcriptase (RT)‐associated ribonuclease H (RNase H) remains as the only enzyme encoded within the viral genome not targeted by current antiviral drugs. In this work, we report the design, synthesis, and biologic evaluation of a novel series of galloyl derivatives with HIV‐1 RNase H inhibitory activity. Most of them showed IC50 s at sub‐ to low‐micromolar concentrations in enzymatic assays. The most potent compound wasII ‐25 that showed an IC50 of 0.72 ± 0.07 μM in RNase H inhibition assays carried out with the HIV‐1BH 10 RT.II ‐25 was 2.8 times more potent than β‐thujaplicinol in these assays. Interestingly, II ‐25 and other galloyl derivatives were also found to inhibit the HIV IN strand transfer activity in vitro. Structure–activity relationships (SAR) studies and molecular modeling analysis predict key interactions with RT residues His539 and Arg557, while providing helpful insight for further optimization of selected compounds. Abstract : A series of galloyl derivatives was designed and synthesized as anti‐HIV‐1 RNase H inhibitors, the most potent compound of which showed an IC50 of 0.72 ± 0.07 μM, 2.8 times more potent than β‐thujaplicinol. SAR studies and molecular modeling analysis provided helpful insight for further optimization of selected compounds.